2022
DOI: 10.1021/acs.energyfuels.2c02560
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Impact of Steam Concentration on the Activity and Stability of Double-Perovskite Air Electrodes for Proton-Conducting Electrolysis Cells

Abstract: Great efforts have been devoted to developing high-performance air electrodes for proton-conducting electrolysis cells (PCECs). However, the stability of existing air electrodes still cannot meet the requirement for practical applications, and the degradation mechanisms require further investigation. Herein, taking porous PrBa 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 5+δ (PBSCF)−BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3−δ (BZCYYb) composite air electrode as the model system, we systematically investigate the impact of steam concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
(65 reference statements)
0
15
0
Order By: Relevance
“…However, a background increase was observed in the PXRD patterns after water vapor treatment, indicating the formation of amorphous hydroxides, which is more obvious after 10.5 bar of pH 2 O for 100 h. This agrees with the recent Pan et al study on PrBa 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 5+ δ (PBSCF)–BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3− δ (BZCYYb) composite positrodes in which they report that high steam concentrations promoted the segregation of Ba and Sr to the surface to form a Sr-OH or Ba-OH phase. 34 The simulation studies show that in the case of perovskites, the surface segregation can be enhanced also by the structural strain. 35 This can suggest that the compositional complexity of BLGC concerning BLnC can play a role in their stability in steam.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, a background increase was observed in the PXRD patterns after water vapor treatment, indicating the formation of amorphous hydroxides, which is more obvious after 10.5 bar of pH 2 O for 100 h. This agrees with the recent Pan et al study on PrBa 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 5+ δ (PBSCF)–BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3− δ (BZCYYb) composite positrodes in which they report that high steam concentrations promoted the segregation of Ba and Sr to the surface to form a Sr-OH or Ba-OH phase. 34 The simulation studies show that in the case of perovskites, the surface segregation can be enhanced also by the structural strain. 35 This can suggest that the compositional complexity of BLGC concerning BLnC can play a role in their stability in steam.…”
Section: Resultsmentioning
confidence: 96%
“…For both samples, the main crystalline products of decomposition at high steam pressures are Gd(OH) 3 and BaCO 3 as well as Co compounds (Co 3 O 4 and Co(OH) 2 ). Though, the existing BaCO 3 is the product of decomposition 34 The simulation studies show that in the case of perovskites, the surface segregation can be enhanced also by the structural strain. 35 This can suggest that the compositional complexity of BLGC concerning BLnC can play a role in their stability in steam.…”
Section: Stability In H 2 Omentioning
confidence: 98%
“…The two doublets can be fitted and assigned to the lattice Sr (Sr lat ), which is the Sr in the lattice of LSCF perovskite and the surface Sr (Sr sur ) that is the Sr on the surface of LSCF. 56 The Sr sur /Sr lat proportion can be used to denote the degree of Sr segregation on the surface, and the results are shown in Fig. 7d.…”
Section: Resultsmentioning
confidence: 99%
“…For a PCEC with the BZCYYb electrolyte displaying great stability for 600 h under moderate humidity of 20% H 2 O at 600 °C, a voltage degradation rate of 30 mV·kh –1 was exhibited and the corresponding EIS analysis indicated that the cell degradation primarily resulted from electrode performance, while no obvious change in ohmic resistance was observed for the BZCYYb electrolyte . However, a sharp increase of ohmic resistance from 0.458 Ω·cm 2 to 0.624 Ω·cm 2 was observed after merely a 90-h operation under 50% H 2 O, illustrating the severe degradation of BZCYYb electrolyte in the highly humidified environment …”
Section: Protonic Ceramic Electrolysis Cells (Pcecs)mentioning
confidence: 96%
“…387 However, a sharp increase of ohmic resistance from 0.458 Ω•cm 2 to 0.624 Ω•cm 2 was observed after merely a 90-h operation under 50% H 2 O, illustrating the severe degradation of BZCYYb electrolyte in the highly humidified environment. 391 Given that the decomposition of BaCe 1−x Zr x O 3 -based materials doped with other elements was still detected when sufficient concentrations of H 2 O and CO 2 were present in the surrounding environments, 392 optimizing the electrolyte structure into a bilayer configuration composed of a protective layer on the anode side to prevent destruction derived from steam and a conductive layer on the cathode side has been proposed as a solution. Typically, the protective layer should be as thin as possible for minimized ohmic resistance and have a dense structure for complete isolation from steam, which is normally fabricated through atomic layer deposition (ALD) and PLD.…”
Section: Degradation Of Electrolytesmentioning
confidence: 99%